Contribution to the knowledge of the fauna of the long-tongued bees (Hymenoptera, Apoidea: Megachilidae, Apidae) in the north of the Arkhangelsk Region - Potapov, GS; Kolosova, YuS (Arctic Environmental Research, 2019)
This article is devoted to a study of the fauna of the long-tongued bees in the north of the Arkhangelsk Region, which is located in the northeast of the European part of Russia, but excludes the Arctic islands. This group includes the bees of the families Megachilidae and Apidae. Forty-four (44) species of bees were found in this region. Most of them (29) are bumblebees (genus Bombus). Fourteen (14) species are megachilid bees (genus Osmia, Coelioxys and Megachile) and one species is Apis mellifera. The largest number of species (39) was recorded in the lower reaches of the Northern Dvina River, due to the long research on this territory. The lowest number of species (16) was recorded in the Mezensky District. In the north of the studied region, the tundra species of B. lapponicus is only presented for the Mezensky District. Many species of bumblebees in the regional fauna belong to the ecological group of the meadow species. These are B. soroeensis, B. ruderarius, B. rupestris and a number of others. They are typical for meadow and ruderal habitats, and are usually not presented in the native taiga habitats. These meadow species are widely represented in the valleys of large rivers, such as the Northern Dvina, the Onega, and the Mezen. Compared to bumblebees, megachilid bees are much rarer in the north of the Arkhangelsk Region. Apis mellifera is presented in the lower reaches of the Northern Dvina River, but here it is rare, compared to the southern part of the Arkhangelsk Region.